PERCEPTIONS OF STUDENT SOFT SKILLS AND SELF EFFICACY ON PERCEPTIONS OF STUDENT WORK READINESS IN SURABAYA - Lavepian, Dian; Wibowo, Januar; Suhandiah, Sri; Supriyanto, Antok (Sekolah tinggi ilmu ekonomi pemuda, 2024)
This research aims to determine and test the influence of Soft Skills and Self Efficacy on Work Readiness and Self Efficacy as mediating variables. This research was conducted on students who are currently taking their final semester and students in Surabaya. This research was raised because undergraduate graduates have increased from year to year, but due to the high demands that must be met to obtain a job and the limited competencies they possess, graduates are not immediately ready to face the world of work. The sample in this study was taken using the Non Probability Sampling method using a saturated sample technique of 130 respondents. The analytical method used is Structural Equation Model (SEM) and uses Partial Least Square (PLS) to test the strength of direct and indirect relationships between various variables. The results of this research prove that soft skills have no effect on work readiness, self-efficacy has a significant effect on work readiness and soft skills have a significant effect on work readiness through self-efficacy.